Enemies of the People: Latin-American Populism, Political Myth, and the Psychodynamics of Conspiracy Thinking - Vassiliou, Phaidon Thymios Benedetti (Επιστήμη και Κοινωνία: Επιθεώρηση Πολιτικής και Ηθικής Θεωρίας, 2017)
This article examines Latin-American populism from a psychonalytical perspective and suggests a possible understanding of the role played by group dynamics, such as group regression and large-group identity, in the rise of conspiracy thinking associated with populist mobilization. It argues that conspiracy thinking is an inextricable feature of populist movements, since both come about as interrelated manifestations of a defensive psychological response intertwined with a preexisting political mythology that resonates in times of institutional crisis, whenever personal and collective identities are at stake.